2019
DOI: 10.1590/1980-549720190022
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados às atividades física e social em amostra de idosos brasileiros: dados do Estudo FIBRA

Abstract: RESUMO: Objetivo: Este trabalho investigou os fatores associados à atividade física em quatro diferentes domínios e o desempenho de atividades sociais em 2.344 idosos (72,3 ± 5,5 anos; 65,6% mulheres) sem déficit cognitivo, residentes na comunidade de seis localidades brasileiras. Método: Uma versão adaptada do Minnesota Leisure Time Activity Questionnaire foi utilizada para avaliar a atividade física em quatro diferentes domínios. Um inventário de atividade social foi desenvolvido para a pesquisa. Idade, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
0
2
0
3
Order By: Relevance
“…This suggests that future studies with a longer follow‐up time will be better able to validate the effect of the intervention. The study also found that the rate of change in scores 3 months after the intervention was slower than that immediately after the intervention, as social participation tends to decline with age (Costa & Neri, 2019). We suggest nurses could incorporate health educational intervention for social participation into routine programs in community care, giving enhanced health education at appropriate intervals.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that future studies with a longer follow‐up time will be better able to validate the effect of the intervention. The study also found that the rate of change in scores 3 months after the intervention was slower than that immediately after the intervention, as social participation tends to decline with age (Costa & Neri, 2019). We suggest nurses could incorporate health educational intervention for social participation into routine programs in community care, giving enhanced health education at appropriate intervals.…”
Section: Discussionmentioning
confidence: 99%
“…Avaliar o nível de atividade física dos idosos institucionalizados e não institucionalizados e relacionar com seu estado nutricional torna-se importante, pois apesar das limitações que podem ocorrer, os idosos podem redescobrir possibilidades de viver sua própria vida com a máxima qualidade possível. Os benefícios da inserção de aporte nutricional adequado e de exercícios físicos na rotina do idoso independente da sua mobilidade, resultam na redução das taxas de morbidade e de mortalidade desta população (Costa & Neri, 2019).…”
Section: Variávelunclassified
“…Facilitating and inhibiting factors are classified into several categories, including economic factors, access factors, and personal characteristics [ 8 ]. In this regard, several studies have investigated the relationship between demographic factors and the social participation of the elderly [ 15 17 ]. Moreover, in a systematic review, Townsend et al identified four major issues that inhibit and facilitate older people’s social participation, including demographic factors (such as age and socioeconomic status), individual/internal factors (such as motivation and health), environmental infrastructure (such as access, transport, and neighborhood), and social networks (especially the size of the existing network) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%